Pre-clinical development of human apurinic/apyrimidinic endonuclease (APE1) inhibitors for cancer therapy - Mohammed, Mohammed Zubair Khuder (2011)
Modulation of DNA base excision repair (BER) has the potential to enhance response to chemotherapy and improve outcomes in tumours such as melanoma, glioma and pancreatic cancer. APE1, a critical protein in BER that processes potentially cytotoxic abasic sites (AP sites), is a promising new target in cancer. In the current study, my aim was to develop small molecule inhibitors of APE1 for cancer therapy. An industry-standard high throughput virtual screening strategy was adopted. The SYBYL8.0 (Tripos, St Louis, MO, USA) molecular modelling software suite was used to build inhibitor templates. Similarity searching strategies were then applied using ROCS 2.3 (Open Eye Scientific, Santa Fe, NM, USA) to extract pharmacophorically related subsets of compounds from a chemically diverse database of 2.6 million compounds. The compounds in these subsets were subjected to docking against the active site of the APE1 model, using the genetic algorithm-based programme GOLD2.7 (CCDC, Cambridge, UK). Predicted ligand poses were ranked on the basis of several scoring functions. The top virtual hits with promising pharmaceutical properties underwent detailed in vitro analyses using fluorescence-based APE1 AP-site cleavage assays and counter screened using endonuclease IV AP-site cleavage assays, fluorescence quenching assays and Whole cell extract AP-site cleavage assays. Biochemical APE1 inhibitors were then subjected to detailed cytotoxicity analyses. Several specific APE1 inhibitors were isolated by this approach. The IC50 for APE1 inhibition ranged between 50 nM and 25 µM. I also demonstrated that APE1 inhibitors lead to accumulation of AP sites in genomic DNA and potentiated the cytotoxicity of alkylating agents in melanoma, glioma and pancreatic cancer cell lines. I have also shown that APE1 inhibitors induce delay in cell cycle progression and caused delay in cancer cell growth. I also demonstrated that APE1 knockdown by shRNA results in decrease cancer cell growth and enhanced cell killing by alkylating agent in Glioma cell line. This PhD project provides evidence that APE1 is an emerging drug target and could have therapeutic application in patients with melanoma, glioma and pancreatic cancer.